Exceptional Case of Spontaneous Ovarian Hyperstimulation Syndrome in Complete Molar Pregnancy: A Case Study - Guimarães, Juliana Barbosa; Bruno, Adriana; Silveira, Márcia Maria Pedreira da; Rodrigues, Andrea Railla Nogueira; Brito, Milena Bastos (Brazilian Journal of Case Reports, 2024)
Spontaneous ovarian hyperstimulation syndrome (OHS) is an uncommon condition. We report the case of a 38-year-old woman admitted to the emergency department with vaginal bleeding, pelvic pain, and an extraordinarily high human chorionic gonadotropin (hCG) level of 1,000,000 mIU/mL. Uterine aspiration confirmed a complete hydatidiform mole. Ten days post-discharge, she returned, exhibiting severe abdominal pain, vomiting, an hCG level of 46,769 mIU/mL, and ultrasound evidence of theca lutein cysts (right ovary: 1329 cm³; left ovary: 500 cm³) along with ascites. Suspected of having OHS, she was hospitalized for clinical management. Treatment included intravenous hydration, analgesia, thromboprophylaxis, and daily laboratory tests, leading to symptomatic improvement despite rising hCG levels. After a 35-day hospital stay, she commenced chemotherapy at a specialized cancer hospital. This case emphasizes the importance of healthcare professionals being alert and aware of the possibility of this diagnostic suspicion in such cases, particularly highlighting the need for hospitalization in moderate to severe instances.